Surface Ozone at Toolik Field Station, Alaska, 2019-2023 ... - Young, Amanda; Helmig, Detlev; Hueber, Jacques; Stahli, Michel (Arctic Data Center, 2023)
Tropospheric ozone is a potent greenhouse gas and air pollutant harmful to humans and vegetation. This atmospheric monitoring at Toolik Field Station is one of the very few ongoing surface ozone monitoring programs located in a tundra environment. This dataset contains the mole fraction of ozone measured in the atmospheric surface layer at Toolik Field Station (68◦38′ N, 149◦36′ W) across four years (2019-2023) at one minute sampling frequency. Measurements were performed using a Thermo Scientific model 49C ultraviolet (UV) absorption analyzer. ...